Security against differential and linear cryptanalysis for general SPT models - Feng-mei LIU; Lian-jun CHEN; Chun-xiang LI; Yan-mei LI; Guo-shuang ZHANG (Tongxin xuebao)
To use SP network in stream ciphers safely and efficiently,the ability against differential and linear cryptanalysis of SPT models was studied,where S and T denote different layers for substitution,in which compression could be achieved,and P denotes the layer for permutation.The upper bound of the maximum differentia lity was given when the branch number of P was optimal,and the upper bound of the maximum linear approximation probability and the maximum linear hull probability are given when the branch number of P was optimal and when S and T were balanced.As a consequence,the problem about evaluating the security against differential and linear cryptanalysis for general SPT models was resolved partially.